Perbedaan Efektifitas Terapi Bermain dan Terapi Musik Terhadap Penurunan Stres Hospitalisasi Pada Anak Usia 4-6 Tahun di Ruang Anak RSU Dr. Soetomo Surabaya Penelitian Quasy Eksperimental - Dewi Indah Porwanti, - (2007)
Hospitalization in pediatric patients may result in anxiety and stress in all age levels. To overcome hospitalization stress in children several techniques can be applied, such as playing therapy and music therapy. This study was intended to find the difference of effectiveness between both therapies in the reduction of hospitalization stress in children aged 4-6 years. This was a quasi-experimental study using pretest posttest design. Samples comprised I 8 respondents, divided into three groups, i.e. the group receiving playing therapy, receiving music therapy, and control. Data were collected using observation sheet, and analyzed statistically using Wilcoxon Signed Rank test and Mann Whitney U Test with significance level ofp _:::: 0.05. The results of statistical test using Wilcoxon Signed Rank test was p = 0.027 for playing therapy, p = 0.024 for music therapy, and p = 0.068 for control. This indicated the influence of playing therapy and music therapy on the reduction of hospitalization stress. Mann Whitney U Test revealed p = 0.009 for playing therapy and control group, p = 0.012 for music therapy and control group, and p = 0.684 for playing therapy and music therapy. This indicated no difference in the effectiveness of playing therapy and music therapy in the reduction of hospitalization stress. Based on the result of data analysis, it can be concluded that playing therapy and music therapy are equally effective in overcoming hospitalization stress in children since both therapies are able to improve emotion to become more positive, thereby reducing hospitalization stress in children.